The impact of methodological and measurement factors on transdiagnostic associations with intolerance of uncertainty: A meta-analysis. (November 2019) - McEvoy, Peter M.; Hyett, Matthew P.; Shihata, Sarah; Price, Jordan E.; Strachan, Laura
Abstract: Intolerance of uncertainty is a dispositional trait associated with a range of psychological disorders, but the influence of methodological factors on theses associations remains unknown. The first aim of this meta-analysis was to quantify the strengths of the association between IU and symptoms of generalised anxiety disorder, social anxiety disorder, panic disorder, agoraphobia, obsessive compulsive disorder, depression, and eating disorders. The second aim was to assess the influence of methodological factors on these relationships, including clinical (vs. non-clinical) status, age group, sex, IU measure, and symptom measure. We extracted 181 studies ( N participants = 52, 402) reporting 335 independent effect sizes (Pearson's r ). Overall, there was a moderate association between IU and symptoms ( r  = 0.51, 95% CI = 0.50–0.52), although heterogeneity was high ( I 2  = 83.50, p  < .001). Some small but significant moderator effects emerged between and within disorders. Effect sizes were not impacted by sample size. The results indicate that IU has robust, moderate associations with a range of disorder symptoms, providing definitive evidence for the transdiagnostic nature of IU. Highlights: Meta-analysed transdiagnostic associations with intolerance of uncertainty (IU) Examined moderators including clinical status, age, sex, IU measure, and symptom measure. Extracted 181 studies (N participants = 52, 402) with 335 independent effects Moderate associations between IU and symptoms were observed across all disorders. Some moderating effects were observed, but these were not substantive.